The immunomodulatory effect of IL-4 accelerates bone substitute material-mediated osteogenesis in aged rats via NLRP3 inflammasome inhibition - Li, Duchenhui; Li, Xiao; Zhang, Jie; Tang, Zhenglong; Tian, Ai (Frontiers in Immunology, 2023)
Alveolar bone defect repair by implanting bone substitute materials is a common clinical treatment used in the field of dental implant restoration. With the understanding of substance¬–immune system interactions and increasing evidence indicating that the postimplantation immune response determines the fate of bone substitute materials, active modulation of host macrophage polarization is considered a promising strategy. However, whether the same regulatory effects exist when an individual immune system is altered with aging is unclear. In this study, we mechanistically investigated the effect of immunosenescence on the active regulation of macrophage polarization by establishing a cranial defect model in young and aged rats implanted with Bio-Oss®. Forty-eight young and 48 aged specific pathogen-free (SPF) male rats were randomly divided into two groups. In the experimental group, 20 μL of IL-4 (5 µg/mL) was injected locally on the third to seventh postoperative days, while an equal volume of PBS was injected in the control group. Specimens were collected at 1, 2, 6, and 12 weeks postoperatively, and bone regeneration at the defect site was evaluated by micro-CT, histomorphometry, immunohistochemistry, double-labeling immunofluorescence, and RT–qPCR. The results indicated that the application of exogenous IL-4 reduced activation of NLRP3 inflammasomes by promoting the polarization of M1 macrophages to M2 macrophages, thus promoting bone regeneration at the site of bone defects in aged rats. However, this effect was gradually weakened after the IL-4 intervention was discontinued. In summary, our data confirmed that a strategy to regulate macrophage polarization is also feasible under conditions of immunosenescence, i.e., the local inflammatory microenvironment can be regulated by reducing M1-type macrophages. However, further experiments are needed to determine an exogenous IL-4 intervention that can maintain a more sustained effect.